Optimalisasi Produk Qardhul Hasan Dalam Memberdayakan Ekonomi Umat - Ferry Khusnul Mubarok (AKUNTABEL, 2019)
This study aims to determine the mechanism of qardhul hasan contract financing, identify empowerment mechanisms through qardhul hasan, and identify qardhul hasan optimization strategies as a place of empowerment. The research method uses a qualitative approach. Primary data sources obtained from interviews, observation and documentation. The results of the study show that the mechanism of qardhul hasan financing at BMT Beringharjo Yogyakarta through several stages starting from the stage of submission, survey, contract, and mentoring. For the mechanism of empowerment through the concept of productive zakat by providing funding facilities, procurement of goods and assistance, and there are classifications based on classes such as QH, SMK, MU and Binar. The optimization strategy is by optimizing funding in the form of optimizing ZIS funds and expanding networks in raising funds both grants, CSR, and endowments, and in terms of lending in the form of optimizing the mentoring process and optimizing the capabilities of human resources both assistants and customers.